2017
DOI: 10.5505/eudfd.2017.40326
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Different Application Procedures on Microleakage and Microhardness of a Bulk-Fill Composite Material

Abstract: ÖZET Amaç: Bu çalışmanın amacı tek tabaka ve tabakalama tekniğiyle uygulanan bulk-fill kompozit rezinin (Tetric Evo Ceram Bulk-Fill; IVW ve IVB, Ivoclar/Vivadent, Liechtenstein) mikrosızıntı ve mikrosertlik özelliklerinin karşılaştırılmasıdır. Yöntem: Çekilmiş 28 adet çürüksüz üçüncü molar diş üzerinde hazırlanan Sınıf I kaviteler (4X4X4mm) sırasıyla 2 ve 4 mm'lik tabakalar halinde iki farklı renkte rezin kompozitle restore edildi. Mikrosızıntı testi için dişler bazik fuksin kullanılarak boya penetrasyonuna ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
0
4
0
1
Order By: Relevance
“…Loss of edge harmony between the tooth tissue and the material, interruption of the connection between the interface, application-related errors, and polymerization shrinkage can all play a role. This situation leads to microleakage, marginal coloration, and secondary caries [ 8 , 10 ]. Mahmoud et al reported that coloration occurring between untreated enamel surfaces and the residual composite surplus could also be a factor [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Loss of edge harmony between the tooth tissue and the material, interruption of the connection between the interface, application-related errors, and polymerization shrinkage can all play a role. This situation leads to microleakage, marginal coloration, and secondary caries [ 8 , 10 ]. Mahmoud et al reported that coloration occurring between untreated enamel surfaces and the residual composite surplus could also be a factor [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, this is a time-consuming process in the case of deep cavities and in the case of contamination between the increments, and carries an increased risk of air bubble development [ 8 ]. Such factors as the resin shade/type filler amount and the intensity and spectrum of the activation light were all found to have a bearing on the cure depth of the resin composite [ 9 , 10 ]. These need to be accompanied by qualities of good adaptation and low residual stress, as required for all materials and filling techniques, and are essential through polymerization [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Uzel ve ark. 41 ise bulk fill kompozitler ile ilgili yaptıkları çalışmada kompozitlerin tek tabaka halinde ve tabakalama tekniği ile kullanımında mikrosızıntı yönünden aralarında istatistiksel olarak anlamlı fark bulamamışlardır.…”
Section: Marjinal Kenar Adaptasyonuunclassified